Study on the Poverty of Traditional Fishermen in Lombonga Village, Balaesang District, Donggala Regency - Moh Fahrun; Dirwan Dirwan; Rajindra Rajindra (International Journal of Health, Economics, and Social Sciences (IJHESS), 2021)
This study examines how the socio-economic life of traditional fishing communities in Lombonga Village, Balaesang District, Donggala Regency. This study aims to determine how the socio-economic conditions of the traditional fishing community in Lombonga Village, Balaesang District, Donggala Regency. To identify the problem, the researcher used the qualitative method in analyzing the problem. Data collection techniques used in this study were through observation, interviews, and documentation. While the data analysis technique used in this study is through data reduction, data presentation, and verification of concluding. Based on the results of the study, the socio-economic life of the traditional fishing community in Lombonga Village, Balaesang District, Donggala Regency is still below the average standard of living of other communities, this is due to the limited facilities and infrastructure owned and also supported by low human resources and fishermen's interest in middlemen. still very high. The income obtained by fishermen is less than optimal in meeting their daily needs, to overcome the economic downturn of traditional fishing communities, it is necessary to reactivate fish auctions and the role of savings and loan cooperatives is needed so that they can provide adequate capital assistance and the distribution of assistance can reach all existing fishermen. It is hoped that with the existence of a fish auction place and the role of savings and loan cooperatives, fishermen can escape from the snares of existing middlemen.